BRICS AS A TRANSREGIONAL ADVOCACY COALITION - Rodrigues Marques da Silva, Roberta; Rodrigues Gomes, Eduardo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In this article, we aim to: (i) review the concepts adopted in the literature to explain the nature and behavior of the BRICS in international relations and (ii) present a new BRICS conceptualization proposal. From the first to the last Summit Conference, the BRICS explicitly advocates a multilateral world order through the inclusion of emerging countries in the base institutions of the Western order. For the elaboration of the article, we review the literature on BRICS, as well as the approach on regionalism proposed by Soderbaum to elaborate our conceptualization of the BRICS as an advocacy coalition.